239 Neurovascular Assessment in Fracture Patients Admitted in a Major Trauma Centre, a Comparison of Emergency Department and Orthopaedic Admission Documentation. (19th August 2022) - Gilmore, C; Toner, E; McHenry, S
Abstract: Aim: The December 2021 British Orthopaedic Association Standards for Trauma for peripheral nerve injuries clearly state "An examination to assess all the functions of a peripheral nerve should be performed and recorded in sufficient detail to allow confident comparison with preceding and subsequent examination". Early accurate neurovascular assessment should first be performed to identify patients requiring urgent surgical intervention, clear documentation is essential to facilitate monitoring over time. The aim of this study was to evaluate the neurovascular documentation in trauma patient's presenting to a Major Trauma Centre and compare quality of Emergency doctors (ED) documentation against Orthopaedic surgeons. Method: A retrospective analysis of A&E and orthopaedic admission proforma paperwork was performed, 77 patients were identified over 4 weeks from Nov – Dec 2020. Following the introduction of vascular examination section to the admission paperwork a repeat cohort of 75 patient notes were reviewed in Oct – Nov 2021. Results: Orthopaedic surgeons were more compliant with neurovascular assessment than ED (96% vs 77%), this was maintained in 2021 (96% vs 70%). Orthopaedic surgeons were more specific when documenting components of vascular, motor function and sensation examination (75% vs 39%). Significant numbers of patients had only 'neurovascularly intact'. Poor documentation post manipulation/splinting was noted, with no documentation in 63% of cases. Conclusions: Neurovascular documentation remains a challenge in the care of orthopaedic trauma patients. Orthopaedic surgeons were consistently more compliant at documentation compared to Emergency doctors. Many patients had a gross assessment with only 'neurovascularly intact' documented, falling below the BOAST standard.